AB0275 The multi-biomarker disease activity score tracks response to rituximab treatment in rheumatoid arthritis patients. (12th June 2018) - Roodenrijs, N.M.T.; de Hair, M.J.H.; Wheater, G.; Elshahaly, M.; Tekstra, J.; Teng, Y.K.O.; Hwang, C.C.; Liu, X.; Sasso, E.H.; van Laar, J.M.
Abstract : Background: A multi-biomarker disease activity (MBDA) score was developed to objectively measure disease activity for patients with rheumatoid arthritis (RA). 1 The MBDA score is calculated by an algorithm using concentrations of 12 serum biomarkers. The MBDA score has been shown to track response to treatment with several DMARDs. 2 4 Objectives: To assess the ability of the MBDA score to track response to rituximab treatment in RA patients. Methods: Data were used from 3 cohorts (1 in the United Kingdom, 2 in the Netherlands) of RA patients treated with rituximab 1000 mg and methylprednisolone 100 mg at days 1 and 15. The MBDA score was assessed in serum samples at baseline (BL, n=57) and at 6 months (n=46). Wilcoxon signed-rank test was used to statistically compare the medians at BL and 6 months. Spearman's rank correlation (ρ) was used to analyse relationships between BL and 6 month values and change (Δ) from BL to 6 months for MBDA score vs. the following endpoints: DAS28-ESR, DAS28-hsCRP, ESR, hsCRP and Health Assessment Questionnaire (HAQ). Logistic regression analysis with adjustment for age, sex, smoking, ACPA and RF was used to assess the association between ΔMBDA score and non-response, using EULAR response categories at Month 6. p<0.05 was considered statistically significant. Results: At baseline the median MBDA score and DAS28-ESR were 54.5 (range 15.0–84.0) and 6.3 (range 2.5–8.4), respectively. The improvement in both scores after 6 months was statistically significant (p=0.003 and p<0.0001, respectively). MBDA score correlated with DAS28-ESR, DAS28-hsCRP, ESR and hsCRP at BL and Month 6 (table 1). ΔMBDA score from BL to Month 6 correlated with changes in these measures, except for the correlation with ΔDAS28-hsCRP (ρ=0.419, p=0.053). Spearman's correlation for ΔMBDA score vs. ΔDAS28-ESR was ρ=0.548, p<0.0001 (table 1). ΔMBDA score also correlated with EULAR non-response (n=39), with adjusted OR=1.115 (95% CI=1.017–1.223, p=0.015), which corresponds to an OR of 2.97 for every 10-unit change in MBDA score. Correlations were not observed between MBDA scores or ΔMBDA score and the corresponding HAQ measurements (table 1). Conclusions: We have shown, for the first time, that the MBDA score tracked disease activity in RA patients treated with rituximab and that change in MBDA score reflected the degree of treatment response. References: [1] Centola M, et al. Development of a Multi-Biomarker Disease Activity Test for Rheumatoid Arthritis. PLoS One2013;8(4). [2] Bakker MF, et al. Performance of a multi-biomarker score measuring rheumatoid arthritis disease activity in the CAMERA tight control study. Ann Rheum Dis. 2012;71(10):1692–7. [3] Jurgens MS, et al. The Multi-biomarker Disease Activity Test for Assessing Response to Treatment Strategies Using Methotrexate with or without Prednisone in the CAMERA Trial-II2014;81–98. ISBN:978–94–6259–393–0. [4] Hirata S, et al. A multi-biomarker disease activity score tracks clinical response consistently in patients with rheumatoid arthritis treated with different anti-tumor necrosis factor therapies: A retrospective observational study. Mod Rheumatol2015;25(3):344–9. Disclosure of Interest: N. Roodenrijs: None declared, M. de Hair: None declared, G. Wheater: None declared, M. Elshahaly: None declared, J. Tekstra: None declared, Y. Teng: None declared, C. Hwang Employee of: Crescendo Bioscience, X. Liu Employee of: Crescendo Bioscience, E. Sasso Shareholder of: Myriad Genetics, Employee of: Crescendo Bioscience, J. van Laar Grant/research support from: Arthrogeen, MSD, Pfizer, Eli Lilly, BMS, Astra Zeneca, Roche-Genentech